Apatites coating in vitro on titanium - influence of the thermal treatment - Vercik, LCD; Assis, C. M. de; Fook, MVL; Santos, M. L. dos; Guastaldi, A. C. (Editora Unesp, 2003)
Commercially pure titanium (cp-Ti), and some of its alloys are considered very important in the medical field because of its excellent biocompatibility and mechanical properties. Recently a simple chemical, method was introduced to induce the bioactivity of these inert metallic materials. In this work, the biomimetic chemical process has been used to modify the cp-Ti surface with the deposit of a layer of apatite. The main objective consisted in studying the influence of the thermal treatment on the evolution of the crystallinity of the deposited phases. X-ray diffraction and scanning electron microscopy techniques showed that the apatite coatings with thermal treatments between 400 and 600 degreesC presented low crystallinity similar to the biological apatites. Above 700 degreesC, the apatite coatings appeared more crystalline, exhibiting a mixture of hydroxyapatite, octacalcium phosphate and magnesium phosphate.
Keywords: biomaterials; titanium; coatings; biomimetic process; hydroxyapatite